2015
DOI: 10.1134/s0022476615040150
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and thermal stability of new iron phosphates KMFe(PO4)2 (M = Ni, Mg, and Co)

Abstract: Three isostructural iron monophosphates KNiFe(PO 4 ) 2 (KNi), KMgFe(PO 4 ) 2 (KMg-LT, where LT means "low-temperature stable phase"), and KCoFe(PO 4 ) 2 (KCo-LT) are synthesized and structurally characterized from X-ray diffraction data. They crystallize in the monoclinic system with the space group P2 1 /c. Their structures have in common a three-dimensional framework, built up by infinite zigzag chains of edge-sharing MO 6 (M = Ni, Mg or Co) octahedra, linked by FeO 5 and PO 4 polyhedra via vertices and edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The calculations were made without considering the splitting of the Na position and 'dilution' of the positions of Zn and Al. study (Badri et al, 2015) revealed a congruent melting of KNiFe(PO 4 ) 2 at 941 C and an irreversible phase transition from the low-to the high-temperature stable phases at 778 and 840 C for isotypic KMgFe(PO 4 ) 2 -LT and KCoFe(PO 4 ) 2 -LT, respectively. For RbCuAl(PO 4 ) 2 , the spontaneous magnetization and antiferromagnetic ordering at T N = 10.5 K was shown (Yakubovich et al, 2016).…”
Section: Tablementioning
confidence: 92%
“…The calculations were made without considering the splitting of the Na position and 'dilution' of the positions of Zn and Al. study (Badri et al, 2015) revealed a congruent melting of KNiFe(PO 4 ) 2 at 941 C and an irreversible phase transition from the low-to the high-temperature stable phases at 778 and 840 C for isotypic KMgFe(PO 4 ) 2 -LT and KCoFe(PO 4 ) 2 -LT, respectively. For RbCuAl(PO 4 ) 2 , the spontaneous magnetization and antiferromagnetic ordering at T N = 10.5 K was shown (Yakubovich et al, 2016).…”
Section: Tablementioning
confidence: 92%
“…Whereas the environments around the two TM sites are tetrahedral in the title compound, an octahedral coordination is found for one site (Co) in the -form. The crystal structure of -KCoFe(PO 4 ) 2 is isotypic with that of KZnFePO 4 ) 2 (Badri et al, 2014), while that of -KCoFe(PO 4 ) 2 is isotypic with those of KNiFe(PO 4 ) 2 and KMgFe(PO 4 ) 2 (Badri et al, 2015).…”
Section: Database Surveymentioning
confidence: 93%
“…The title compound crystallizes isotypically with KZnFe(PO 4 ) 2 (Badri et al, 2015). The principal building units of -KCoFe(PO 4 ) 2 are shown in Fig.…”
Section: Structural Commentarymentioning
confidence: 99%